Asuhan Keperawatan Gerontik Pada Pasien Dengan Gastritis di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Lola Agustin; Sandra Dewi; Armaita Armaita; Prima Yoselina (CV. ITTC INDONESIA, 2026)
Gastritis is an inflammation of the gastric mucosa that commonly occurs, especially among the elderly, due to irregular eating patterns, Helicobacter pylori infection, and increased gastric acid production. According to World Health Organization (WHO) data in 2022, approximately 40%–50% of the global population has experienced gastritis, equivalent to around 1.6 billion cases worldwide. Data from the Tresna Werdha Sabai Nan Aluih Social Institution in 2025 showed 15 cases of gastritis out of 110 diseases among elderly residents, indicating that gastritis remains a significant health problem requiring special attention. The purpose of this scientific paper was to provide gerontic nursing care for patients with gastritis. The method used was a case study approach applying the nursing process, including assessment, nursing diagnosis, intervention planning, implementation, evaluation, and documentation conducted on Mr. A at the Tresna Werdha Sabai Nan Aluih Social Institution, Padang Pariaman Regency, from February 11–16, 2026. Assessment results showed moderate epigastric pain, sleep disturbances, and decreased appetite. Nursing diagnoses included chronic pain, impaired comfort, and ineffective health management. Interventions provided were health education, dietary regulation, deep breathing relaxation techniques, and support for therapy adherence. After five days of nursing care, the patient’s condition improved, marked by reduced pain intensity, better sleep quality, and increased knowledge in managing health independently.